DESIGN STUDY PRESSURIZED WATER REACTOR (PWR) USING COMBINATION THORIUM-URANIUM FUEL CYCLE - (nim : 10209049), ROUF
Pressurized water reactor (PWR) is the most common reactor which used as a commercial power reactor in the world. Generally, PWR used 1,5 – 5 % enriched natural uranium as fuel. Commonly, reactor which used this kind of fuel encounter waste processing problem and nonproliferation resistance. To solve this problem we can use thorium based fuel. In this research, the experiment with a PWR reactor that used thorium based fuel has conducted. The neutronic analysis is performed by using multi-group diffusion equation. The calculation using SRAC Code System begins with cell calculation (PIJ) of UO2 and ThO2 separately with ten years of burn up step. From that calculation we get multiplication factor and burn-up history. Then, we calculate the reactor core using CITATION module in SRAC Code System, using combination of thorium – uranium fuel cycle with two type of core reactor. First core reactor content of (Th-U)O2 fuel and has different enrichment in 3 core region. First core type has optimized at 50% fuel fraction and 35% composition of UO2 inside (Th-U)O2 fuel. Another core type is a heterogeneous core with (Th-U)O2 and UO2 fuel at different region. Uranium enrichment at (Th-U)O2 fuel is higher than conventional PWR to supply neutron for thorium. From this CITATION calculation, we also get the multiplication factor and neutron flux and power density distribution of the core reactor. At optimized core, operation time for first core is 9 years with Pu production 4 times less than conventional PWR. Meanwhile, we get 4 years operation time for second core type with Pu production 2 times less than conventional PWR.